Leading while Muslim : the experiences of American Muslim principals after 9/11 - Almontaser, Debbie (Rowman & Littlefield, 2019)
"The book explores the lived experiences of 14 American Muslim public school principals post-9/11 and the impact of global events, political discourse, and media coverage of Islam and Muslims on one's leadership ability and spirituality"--